Integrating enterprise risk management and green intellectual capital as catalysts for sustainability performance in the energy transition in Southeast Asia - Dewi Cahyani Pangestuti (Journal of Law, Administration, and Social Science, 2026)
This study investigates the roles of Enterprise Risk Management (ERM) and Green Intellectual Capital (GIC) in driving corporate sustainability within the energy sector in Southeast Asia. A comprehensive synthesis of the literature reveals that the implementation of robust ERM frameworks encompassing financial, political, operational, environmental, and social risks, including Environmental, Social, and Governance (ESG) dimensions enhances firms’ capabilities to identify and mitigate risks in a more holistic and integrated manner. The findings indicate that GIC, particularly green human capital and green structural capital, serves as a positive driver of sustainability performance by strengthening the relationship between managerial capacity and corporate environmental performance. However, the role of green relational capital remains ambiguous and warrants further empirical investigation. Moreover, the integration of ERM with regional policies, cross-border cooperation, and the adoption of digital technologies provides strategic pathways for achieving a more efficient and sustainable energy transition. The study highlights sectoral differences between renewable and fossil energy firms in addressing climate risk costs, as well as the critical importance of coordinated policies and regulatory frameworks in supporting risk mitigation and sustainability initiatives. The theoretical contribution of this research lies in the integration of resource-based theory, stakeholder theory, and natural resource orchestration theory to explain the mechanisms through which ERM and GIC jointly enhance sustainability performance. Practically, the study offers policy and managerial recommendations emphasizing the alignment of risk management strategies, incentives for GIC development, and the adoption of innovative technologies to strengthen resilience and operational efficiency in the energy sector.